Perceptions of Spanish students and teachers: facts about tablets - Sánchez-Jiménez, José (2019)
This study focused on knowing the perceptions of the users of this technology and its use in Spanish courses to make the necessary adjustments after three years of its introduction. Arlington Public Schools took on the task of tempering the needs with the use of tablets in all its academic courses at all school levels. Educational interaction between students and teachers has been altered by the adaptation and integration of technology in recent decades. As advances in technology advance, all parts of the educational communities have been tempered in terms of their functioning and how they have begun to create a new education and have focused on its implementation process as a tool or teaching instrument. Know the feeling of the educational entity in the use of tablets in their curricula and how it influences the ways of teaching in Spanish courses. The fears, challenges, needs and insecurities of the users will be considered when making the changes towards an integrating curriculum with technology and Spanish.